Measuring the Impact of General Allocation Funds, Labor and Government Expenditures on Economic Growth - Andi Lopa Ginting (EcceS (Economics, Social, and Development Studies), 2021)
This study aims to analyze the effect of General Allocation Funds, Labor and Government Expenditures on Economic Growth in East Kotawaringin Regency. The research method used in this research is a descriptive-quantitative research approach. The analytical tool used in his study is multiple linear regression with the t test, F test, and the coefficient of determination test. The results of this study indicate that partially the variables of the General Allocation Fund and Government Expenditures have a significant effect on Economic Growth in East Kotawaringin Regency. While the Labor variable does not have a significant effect on Economic Growth in East Kotawaringin Regency. Simultaneously, the variables of the General Allocation Fund, Labor, and Government Expenditures together have an effect on the Economic Growth variable. The implications of this research include, among others, to encourage the economy of East Kotawaringin Regency, the general allocation fund should be increased for the advancement and improvement of economic growth as well as improving the quality of the Laborforce in the East Kotawaringin area.Keywords:   Economic Growth; General Allocation Fund; Government Expenditure; Labor